2017
DOI: 10.18632/oncotarget.15435
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 19 promoter directs the expression of Cre recombinase in various epithelia of transgenic mice

Abstract: Cytokeratin 19 (K19) is expressed in various differentiated cells, including gastric, intestinal and bronchial epithelial cells, and liver duct cells. Here, we generated a transgenic mouse line, K19-Cre, in which the expression of Cre recombinase was controlled by the promoter of K19. To test the tissue distribution and excision activity of Cre recombinase, K19-Cre transgenic mice were bred with Rosa26 reporter strain and a mouse strain that carries PTEN conditional alleles (PTENLoxp/Loxp). At mRNA level, Cre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Cytokeratins (CKs) are intermediate filament proteins mainly expressed in epithelial cells and composed of type I (CK9‐20) and type II (CK1‐8) cytokeratins . Previous studies have demonstrated that CKs played a critical role in maintaining epithelial barriers, regulating innate immunity, intracellular signaling, cell adhesion, epithelial cell proliferation, and differentiation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokeratins (CKs) are intermediate filament proteins mainly expressed in epithelial cells and composed of type I (CK9‐20) and type II (CK1‐8) cytokeratins . Previous studies have demonstrated that CKs played a critical role in maintaining epithelial barriers, regulating innate immunity, intracellular signaling, cell adhesion, epithelial cell proliferation, and differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…Cytokeratins (CKs) are intermediate filament proteins mainly expressed in epithelial cells and composed of type I (CK9-20) and type II (CK1-8) cytokeratins. 5 Previous studies have demonstrated that CKs played a critical role in maintaining epithelial barriers, regulating innate immunity, intracellular signaling, cell adhesion, epithelial cell proliferation, and differentiation. 6 Among them, cytokeratin 7 (CK7)is expressed in various tissue types, such as intestine crypt, pancreatic ducts, mammary gland ducts, and liver bile ducts but absent in hepatocytes.…”
mentioning
confidence: 99%
“…Therefore, we performed a meta-and bioinformatics analysis about PTEN expression in gastric cancer at both mRNA and protein levels in the following work. Gastric precancerous lesions appear between gastric epithelium and adenocarcinoma, and are divided into adenomatous, regenerative, crysptal and globoid dysplasia [50]. Jang et al [51] reported that nuclear PTEN expression was gradually down-regulated during colorectal mucosa-adenoma-adenocarcinomametastasis sequence.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature [ 52 ], precancerous lesions appear from gastric epithelium to adenocarcinoma, including adenomatous, regenerative, crysptal or globoid dysplasia. Consistent with the data about breast, colonic, bladder and gastric cancers [ 15 , 27 ], we found down-regulated maspin expression in gastric cancer, compared with gastric mucosa or dysplasia in the present study, suggesting that maspin hypoexpression contributed to gastric carcinogenesis as a late event.…”
Section: Discussionmentioning
confidence: 99%